Kerjasama Perpustakaan FISIP Unpad dengan Bank BRI melalui Fasilitas Creative Hub and Knowledge Center - Romdona, Wisna (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This research was conducted to find out how collaboration can be established between the Library of the Faculty of Social and Political Sciences, Universitas Padjadjaran (FISIP Unpad) and Bank BRI in building the Creative Hub and Knowledge Center facility. In recent times, collaboration is a necessity, it is no longer an optional consideration. Considering the important role of collaboration between one institution and another, especially collaboration in academic libraries, I am interested in bringing up this topic. In the midst of many limitations and challenges faced by academic libraries, collaboration with other parties can be an alternative solution to overcome this problem. This research method used a qualitative approach with data collection techniques through observation and in-depth interviews with related parties that knew how this collaboration came to existence. The result shows that this collaboration is a form of BRI Bank's Corporate Social Responsibility (CSR) to the Faculty of Social and Political Sciences, Universitas Padjadjaran (FISIP Unpad) through the Creative Hub & Knowledge Center facility with various stages of collaboration. The existence of this new facility brings many benefits to the academic community of Universitas Padjadjaran as well as Bank BRI.